2019
DOI: 10.1177/0963689719851772
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Stellate Cells Facilitate Perineural Invasion of Pancreatic Cancer via HGF/c-Met Pathway

Abstract: Pancreatic cancer (PC) is a highly lethal cancer that has a strong ability for invasion and metastasis, poor prognosis, and a stubbornly high death rate due to late diagnosis and early metastasis. Therefore, a better understanding of the mechanisms of metastasis should provide novel opportunities for therapeutic purposes. As a route of metastasis in PC, perineural invasion (PNI) occurs frequently; however, the molecular mechanism of PNI is still poorly understood. In this study, we show that the hepatocyte gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…A common adverse feature of pancreatic cancer is neural invasion (NI) [ 90 ]. NI is the pathological process in which cancer cells invade through the nerve or its surroundings and is generally associated with a poor prognosis [ 90 , 91 ]. Studies in patients have revealed that tumors with high nerve growth factor (NGF) expression levels exhibit more frequent NI [ 92 ].…”
Section: Cafs Modulate the Immune Microenvironment And Crosstalk Wmentioning
confidence: 99%
See 1 more Smart Citation
“…A common adverse feature of pancreatic cancer is neural invasion (NI) [ 90 ]. NI is the pathological process in which cancer cells invade through the nerve or its surroundings and is generally associated with a poor prognosis [ 90 , 91 ]. Studies in patients have revealed that tumors with high nerve growth factor (NGF) expression levels exhibit more frequent NI [ 92 ].…”
Section: Cafs Modulate the Immune Microenvironment And Crosstalk Wmentioning
confidence: 99%
“…In vitro experiments revealed that CAFs secrete HGF, which subsequently increases the expression of NGF in cancer cells. In the presence of CAF-conditioned media, pancreatic cancer cells were able to successfully migrate towards dorsal root ganglia (DRG), whereas knock-down of NGF or HGF significantly reduced the migration, highlighting the importance of CAFs in NI [ 91 , 93 ].…”
Section: Cafs Modulate the Immune Microenvironment And Crosstalk Wmentioning
confidence: 99%
“…Additionally, this HGF-induced FAK activation also upregulates MMP-1, MMP-9, MMP-14 (all of these MMPs play an important role in cell invasion, thus increasing invasiveness of cancer) in gallbladder, prostate, and liver cancers [63][64][65]. Recent studies have also demonstrated that PSCs facilitate perineural invasion of pancreatic cancer and this process is mediated via the HGF/c-MET pathway [66].…”
Section: Role Of Hgf/c-met Pathway In Hypoxia Angiogenesis Metastasismentioning
confidence: 99%
“…Li et al demonstrated that activated PSCs induced neurite outgrowth towards PCCs and promoted neural invasion of PCCs ( 143 ). More recently, Nan et al reported that PSCs promoted the perineural invasion of PCCs via the HGF/c-Met pathway ( 67 ). In addition, Han et al reported that PSCs contributed to pain in PDAC by PSC-induced secretion of pain factors from dorsal root ganglia ( 144 ).…”
Section: The Role Of Pscs In the Aggressiveness Of Pdacmentioning
confidence: 99%